Nutraceuticals against Oxidative Stress in Autoimmune Disorders - Carmen Mannucci; Marco Casciaro; Emanuela Elisa Sorbara; Fabrizio Calapai; Eleonora Di Salvo; Giovanni Pioggia; Michele Navarra; Gioacchino Calapai; Sebastiano Gangemi (MDPI AG, 2021)
Antioxidant mechanisms are constituted of enzymes, endogenous, and non-enzymatic, exogenous, which have the role of counterbalancing oxidative stress. Intake of these compounds occurs in the diet. Vegetables, plants, and fruits contain a wide range of alkaloids, polyphenols, and terpenoids which are called "phytochemicals". Most of these substances are responsible for the positive properties of fruits and vegetables, which are an essential part of a healthy life with roles in ameliorating chronic illnesses and favoring longevity. Nutraceuticals are substances contained in a food or fragment of it influencing health with positive effects on health helping in precenting or treating disorders. We conducted a review illustrating the principal applications of nutraceuticals in autoimmune disorders. Literature reported several studies about exogenous dietary antioxidant supplementation in diverse autoimmune diseases such as rheumatoid arthritis, lupus, diabetes, and multiple sclerosis. In these pathologies, promising results were obtained in some cases. Positive outcomes were generally associated with a reduction of oxidative stress parameters and a boost to antioxidant systems, and sometimes with anti-inflammatory effects. The administration of exogenous substances through food derivates or dietary supplements following scientific standardization was demonstrated to be effective. Further bias-free and extended studies should be conducted that include ever-increasing oxidative stress biomarkers.